Solvent-free polymer electrolytes - I. Preparation and characterization of polymer electrolytes having pores filled with viscous P(EO-EC)/LiCF3SO3 - Jeon, JD; Kwak, SY; Cho, BW (ELECTROCHEMICAL SOC INC, 2005)
We have attempted to combine a typical gel (hybrid liquid-solid system) and a typical solvent-free polymer electrolyte (solid system) through the concept of the pore-filling polymer electrolyte; instead of organic solvents, a viscous polymer complexed with a Li salt is filled into the pores of a porous membrane. The viscous polymer, poly(ethylene oxide-ethylene carbonate) copolymer [P(EO-EC)] with a low molecular weight (Mw = 1800) and amorphous nature is synthesized using ethylene carbonate (EC) and its viscosity is found to be independent of shear rate, which is a characteristic of a Newtonian fluid. Porous membranes consisting of poly(vinylidene fluoride-co-hexafluoropropylene) [P(VdF-HFP)] and P(EO-EC) are prepared by a phase inversion method and examined by means of H-1 solid-state nuclear magnetic resonance and field emission-scanning electron microscopy. From these results, it is confirmed that they are homogenous on a scale of a few tens of nanometers and the existence of P(EO-EC) in membranes makes much larger pore size and higher porosity than the pure P(VdF-HFP) membrane. This implies that the relative composition of P(EO-EC) plays a critical role in determining the membrane's morphology and porosity. The temperature dependence of the ionic conductivity for the polymer electrolytes is well fitted to the Arrhenius equation. The highest conductivity of 3.7 x 10(-5) S cm(-1) at 25 degrees C and 1.6 x 10(-4) S cm(-1) at 55 degrees C is obtained for E-V6E4. Cyclic voltammetry on stainless steel electrodes shows that the polymer electrolyte is electrochemically stable up to at least 5.0 V vs Li/Li+. (c) 2005 The Electrochemical Society.
Keywords: IONIC-CONDUCTIVITY; ETHYLENE CARBONATE; ELECTROCHEMICAL CHARACTERIZATION; LITHIUM BATTERIES; GEL ELECTROLYTES; BLENDS; METHACRYLATE); IONOMER